MicroRNA‐122 regulates polyploidization in the murine liver. Issue 2 (12th May 2016) - Hsu, Shu‐hao; Delgado, Evan R.; Otero, P. Anthony; Teng, Kun‐yu; Kutay, Huban; Meehan, Kolin M.; Moroney, Justin B.; Monga, Jappmann K.; Hand, Nicholas J.; Friedman, Joshua R.; Ghoshal, Kalpana; Duncan, Andrew W.
Abstract : A defining feature of the mammalian liver is polyploidy, a numerical change in the entire complement of chromosomes. The first step of polyploidization involves cell division with failed cytokinesis. Although polyploidy is common, affecting ∼90% of hepatocytes in mice and 50% in humans, the specialized role played by polyploid cells in liver homeostasis and disease remains poorly understood. The goal of this study was to identify novel signals that regulate polyploidization, and we focused on microRNAs (miRNAs). First, to test whether miRNAs could regulate hepatic polyploidy, we examined livers from Dicer1 liver‐specific knockout mice, which are devoid of mature miRNAs. Loss of miRNAs resulted in a 3‐fold reduction in binucleate hepatocytes, indicating that miRNAs regulate polyploidization. Second, we surveyed age‐dependent expression of miRNAs in wild‐type mice and identified a subset of miRNAs, including miR‐122, that is differentially expressed at 2‐3 weeks, a period when extensive polyploidization occurs. Next, we examined Mir122 knockout mice and observed profound, lifelong depletion of polyploid hepatocytes, proving that miR‐122 is required for complete hepatic polyploidization. Moreover, the polyploidy defect in Mir122 knockout mice was ameliorated by adenovirus‐mediated overexpression of miR‐122, underscoring the critical role miR‐122 plays in polyploidization. Finally, we identified direct targets of miR‐122 ( Cux1, Rhoa, Iqgap1, Mapre1, Nedd4l, and Slc25a34 ) that regulate cytokinesis. Inhibition of each target induced cytokinesis failure and promoted hepatic binucleation. Conclusion: Among the different signals that have been associated with hepatic polyploidy, miR‐122 is the first liver‐specific signal identified; our data demonstrate that miR‐122 is both necessary and sufficient in liver polyploidization, and these studies will serve as the foundation for future work investigating miR‐122 in liver maturation, homeostasis, and disease. (Hepatology 2016;64:599‐615)